Narratives of melancholy: a humanities approach to depression. - Flynn, Deborah (Medical humanities, 2010)
This paper explores narrative literature as a means of inquiry into the sense of self in depression. Described as a disease, an identity and a way of life, depression is influenced by both internal and external factors. Although brain research has provided new insight into the relationship between neurotransmitter function and depression, the symptoms are experienced by individuals whose lives are intertwined with historical and sociocultural interpretations of illness and its manifestations. At the intersection of science and the humanities, narratives aid in the interpretation of lived experiences, provide a window to that experience, and a public medium that engages writers and readers as they interpret the world. Engaging narratives to interpret both experience and medical jargon may reveal for both those experiencing depression and those engaged in their care, a way of mediating that experience. Narratives can help dissect and thus illuminate the official language of medicine and psychiatry and the personal language of depression. Such a window can enhance the opportunities for empathy and care.
11 citations (Crossref) [2023-10-31] Place: United States Flynn, Deborah. Department of Public Health, Southern Connecticut State University, 144 Farnham Avenue, New Haven, CT 06515, USA. flynnd1@southernct.edu
Keywords: *Depressive Disorder/hi [History]; *Humanities; *Narration; Depression; Depression/hi [History]; Depressive Disorder; Female; History; 18th Century; History; 19th Century; History; 20th Century; Humanities; Humans; Literature and medicine; Male; Narration; Self Concept; article; depression; dept.pch; female; history; human; humanities; male; narrative medicine; patient narrative; psychiatry; self concept; verbal communication